Learning complexity-boundet rule-based classifiers by combining association analysis and genetic algorithms - Yi, Y.; Hüllermeier, Eyke (in Proceedings EUSFLAT-2005 4th International Conference on the European Society for Fuzzy Logic and Technology, Barcelona, Spain)

Fuzzy sets in machine learning and data mining: Status and prospects - Hüllermeier, Eyke (Fuzzy Sets and Systems)

Experience-based decision making: A satisficing decision tree approach - Hüllermeier, Eyke (IEEE Transactions on Systems, Man and Cybernetics-Part A: Systems and Humans)

Clustering of gene expression data using a local shape-based similarity measure - Balasubramaniyan, R.; Hüllermeier, Eyke; Weskamp, N.; Kämper, J. (Bioinformatics)

HGB: Basiswissen einschließlich Wechsel- und Scheckrecht Fälle und Lösungen auf interaktiver CD - Krimphove, Dieter

A Low Power Design for Embedded DRAMs with Online Consistency Checking - Oehler, Philipp; Hellebrand, Sybille
Keywords: WORKSHOP

Dynamic Routing: A Prerequisite for Reliable NoCs - Ali, Muhammad; Welzl, Michael; Hellebrand, Sybille
Keywords: WORKSHOP

Power Consumption Versus Error Correcting Capabilities in Embedded DRAMs - A Case Study - Oehler, Philipp; Hellebrand, Sybille
Keywords: WORKSHOP

The use of instant messaging in working relationship development: A case study - Trier, Matthias; Cho, Hee-Kyung; Kim, Eunhee (Journal of Computer-Mediated Communication)

IT-gestützte Modellierung und Analyse elektronischer Expertengemeinschaften (Modeling and Evaluation of Electronic Expert Communities) - Trier, Matthias (i-com)

Process-Oriented Production of Learning Units for Sustainable E-Learning Offerings - Müller, Claudia; Trier, Matthias; Herzog, Michael A. (E-Learning)

A Tool for IT-supported Visualization and Analysis of Virtual Communication Networks in Knowledge Communities - Trier, Matthias (Wirtschaftsinformatik 2005)

A Procedural Model for the Production of Reusable and Standard-Compliant E-Learning Offerings - Müller, Claudia; Trier, Matthias (Wirtschaftsinformatik 2005)

IT-Supported Visualization of Knowledge Community Structures - Trier, Matthias (Proceedings of the 38th Annual Hawaii International Conference on System Sciences)

Netzwerkorientiertes Wissensmanagement und seine Unterstützung durch Softwarewerkzeuge - Krallmann, Hermann; Trier, Matthias (Strategisches Wertschöpfungsmanagement in dynamischer Umwelt: Festschrift für Erich Zahn)

Adaptive scheduling for heterogeneous traffic flows in cellular wireless OFDM-FDMA systems - Valentin, Stefan; Gross, James; Karl, Holger; Wolisz, Adam (10th IFIP International Conference on Personal Wireless Communications/PWC'05, Comar, France, 2005)

Periodic real-time scheduling for FPGA computers - Danne, Klaus; Platzner, Marco (Proceedings of the Third International Workshop on Intelligent Solutions in Embedded Systems (WISES))

Memory-demanding Periodic Real-time Applications on FPGA Computers - Danne, Klaus; Platzner, Marco (Work-in-Progress Proceedings of the 17th Euromicro Conference on Real-time Systems (ECRTS))

A heuristic approach to schedule periodic real-time tasks on reconfigurable hardware - Danne, Klaus; Platzner, Marco (Proceedings of the 15th International Conference on Field Programmable Logic and Applications (FPL))

Quasiparticle bands and optical spectra of highly ionic crystals: AlN and NaCl - Bechstedt, F.; Seino, K.; Hahn, P. H.; Schmidt, Wolf Gero (Physical Review B)

Attracted by Long-Range Electron Correlation: Adenine on Graphite - Ortmann, F.; Schmidt, Wolf Gero; Bechstedt, F. (Physical Review Letters)

Calculation of reflectance anisotropy for semiconductor surface exploration - Schmidt, Wolf Gero (physica status solidi (b))

Quasiparticle and excitonic effects in the optical spectra of diamond, SiC, Si, GaP, GaAs, InP, and AlN - Hahn, P. H.; Seino, K.; Schmidt, Wolf Gero; Furthmüller, J.; Bechstedt, F. (physica status solidi (b))

VUV-ellipsometry on GaN: Probing conduction band properties by core level excitations - Esser, N.; Rakel, M.; Cobet, C.; Schmidt, Wolf Gero; Braun, W.; Cardona, M. (physica status solidi (b))

Initial Stage of Si(001) Surface Oxidation from First-Principles Calculations - Fuchs, F.; Schmidt, Wolf Gero; Bechstedt, F. (The Journal of Physical Chemistry B)

Understanding the optical anisotropy of oxidized Si(001) surfaces - Fuchs, F.; Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)

Coulombic Amino Group-Metal Bonding: Adsorption of Adenine on Cu(110) - Preuss, M.; Schmidt, Wolf Gero; Bechstedt, F. (Physical Review Letters)

Conformation-selective adsorption of 2,3-butanediol on Si(001) - Seino, K.; Schmidt, Wolf Gero (Surface Science)

Second-harmonic polarizability including electron-hole attraction from band-structure theory - Leitsmann, R.; Schmidt, Wolf Gero; Hahn, P. H.; Bechstedt, F. (Physical Review B)

Optical response ofπ-conjugated molecular monolayer adsorbed on the semiconductor Si(001) surface: A first-principles study - Hermann, A.; Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)

Phenanthrenequinone Adsorbed on Si(001): Geometries, Electronic Properties, and Optical Response - Hermann, Andreas; Schmidt, Wolf Gero; Bechstedt, Friedhelm (The Journal of Physical Chemistry B)

Optical Absorption of Water: Coulomb Effects versus Hydrogen Bonding - Hahn, P. H.; Schmidt, Wolf Gero; Seino, K.; Preuss, M.; Bechstedt, F.; Bernholc, J. (Physical Review Letters)

A study of impact of inband signalling and realistic channel knowledge for an example dynamic OFDM-FDMA system - Gross, James; Valentin, Stefan; Karl, Holger; Wolisz, Adam (European Transactions on Telecommunications)

Molecular electronic excitations calculated from a solid-state approach: Methodology and numerics - Hahn, P. H.; Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)

Von der Ontologie zur Begriffsanalytik. Kants Beitrag zu den aktuellen Diskussionen über Metaphysik und Ontologie - Ficara, Elena (Philosophie von Immanuel Kant und die Gegenwart)

Vorwort - Peckhaus, Volker (Oskar Becker und die Philosophie der Mathematik)
Rezensionen: History and Philosophy of Logic 27 (2006), 198–200 (Dirk Schlimm); Bulletin of Symbolic Logic 12 (2006), 137–139 (R. Vilkko); NTM 15 (2007), 67–68 (K. Radbruch); Philosophiques 35 (2008), 612–613 (Y. Gauthier).

Einleitung: Oskar Becker und die Philosophie der Mathematik - Peckhaus, Volker (Oskar Becker und die Philosophie der Mathematik)

Rationalismus zwischen Vision und Wirklichkeit. Descartes, Leibniz und die Grenzen des Machbaren - Peckhaus, Volker (ForschungsForum Paderborn)

Comparison of Performance and Realization Effort of a Very Sparse Matrix Converter to a Voltage DC Link PWM Inverter with Active Front End - Round, Simon; Schafmeister, Frank; Pereira, Eduardo; Serpa, Leonardo; Kolar, Johann (Proc. 5th IEEJ International Power Electronics Conference (IPEC))

Analytical Calculation of the Conduction and Switching Losses of the Conventional Matrix Converter and the (Very) Sparse Matrix Converter - Schafmeister, Frank; Rytz, Christoph; Kolar, Johann (Proc. 20th IEEE Applied Power Electronics Conference (APEC))

Enhanced Control Scheme for Three-Phase, Three-Level Rectifiers at Partial Load - Ide, Peter; Schafmeister, Frank; Fröhleke, Norbert; Grotstollen, Horst (IEEE Transactions on Industrial Electronics)

Design and implementation of a hybrid energy supply system for railway vehicles - Li, R.; Pottharst, A.; Fröhleke, N.; Böcker, Joachim; Witting, K.; Dellnitz, M.; Znamenshchykov, O.; Feldmann, R. (Twentieth Annual IEEE Applied Power Electronics Conference and Exposition, 2005. APEC 2005.)

Design of Long-Stator Linear Motor Drives for RailCab Test Track - Grotstollen, H. (Journal of Power Electronics (JPE))

Convoy Operation of Linear Motor Driven Railway Vehicles, Kobe - Awaji, Japan - Henke, C.; Vöcking, H.; Böcker, Joachim; Fröhleke, N.; Trächtler, A. (LDIA 2005, The Fifth International Symposium on Linear Drives for Industry Applications)

Simulation of Power Electronic Circuits - Grotstollen, H.; Böcker, Joachim; Fröhleke, N. (ICSC 2005, Peking, China)

ZVZCS Isolated Converter for Renewable Energy System with Extra Wide Voltage Range - Li, R.; Fröhleke, N.; Böcker, Joachim; Ide, P. (International PCIM Conference 2005, Nürnberg, Deutschland)

Distributed Control Structure of the NBP Test Track with Linear Motor Driven Vehicles - Pottharst, A.; Grotstollen, H. (International Embedded Systems Symposium, Manaus, Brasil)

Impliziert Widerspruchsfreiheit Existenz? Oskar Beckers Kritik am formalistischen Existenzbegriff - Peckhaus, Volker (Oskar Becker und die Philosophie der Mathematik)

Becker und Zermelo - Peckhaus, Volker (Oskar Becker und die Philosophie der Mathematik)

19th Century Logic: Between Philosophy and Mathematics (Wiederabdruck) - Peckhaus, Volker (Mathematics and the Historian’s Craft. The Kenneth O. May Lectures)

Algèbre de la logique, théorie de la quantification et carré des oppositions - Peckhaus, Volker (La quantification dans la logique moderne)

Calculus Ratiocinator vs. Characteristica Universalis? The Two Traditions in Logic, Revisted (Wiederabdruck) - Peckhaus, Volker (Gottlob Frege. Critical Assessments of Leading Philosophers, Bd. 1: Frege’s Philosophy in Context)
Rezension: Zbl. Math. 1100.03006 (I. Grattan-Guinness)

Wahlfolge - Peckhaus, Volker (Historisches Wörterbuch der Philosophie, Bd. 12: W–Z)

Wahrheitsfunktion; Wahrheitstafel - Peckhaus, Volker (Historisches Wörterbuch der Philosophie, Bd. 12: W–Z)

Widerspruchsfreiheit - Peckhaus, Volker (Historisches Wörterbuch der Philosophie, Bd. 12: W–Z)

Wohlordnungssatz - Peckhaus, Volker (Historisches Wörterbuch der Philosophie, Bd. 12: W–Z)

Bochenski, Joseph Maria - Peckhaus, Volker (Enzyklopädie Philosophie und Wissenschaftstheorie, Bd. 1: A–B)

Bachmann, Karl Friedrich - Peckhaus, Volker (Enzyklopädie Philosophie und Wissenschaftstheorie, Bd. 1: A–B)

Zirkel - Peckhaus, Volker (Historisches Wörterbuch der Philosophie, Bd. 12: W–Z)

Aegidius Romanus - Peckhaus, Volker (Enzyklopädie Philosophie und Wissenschaftstheorie, Bd. 1: A–B)

Bachmann, Friedrich - Peckhaus, Volker (Enzyklopädie Philosophie und Wissenschaftstheorie, Bd. 1: A–B)

distinctio - Peckhaus, Volker (Enzyklopädie Philosophie und Wissenschaftstheorie, Bd. 2: C–F)

Dee, John - Peckhaus, Volker (Enzyklopädie Philosophie und Wissenschaftstheorie, Bd. 2: C–F)

Fermat, Pierre de - Peckhaus, Volker; Barner, Klaus (Enzyklopädie Philosophie und Wissenschaftstheorie, Bd. 2: C–F)

Futurabilien - Peckhaus, Volker (Enzyklopädie Philosophie und Wissenschaftstheorie, Bd. 2: C–F)

ens rationis - Peckhaus, Volker (Enzyklopädie Philosophie und Wissenschaftstheorie, Bd. 2: C–F)

Regelung permanent erregter Synchronmaschinen ohne mechanischen Geber für den industriellen Einsatz - Kiel, J.

Automatisierte Inbetriebnahme der Drehzahlregelung für rotierende Direktantriebe mit hohen Rundlaufanforderungen - Wertz, H.

Energietechnik und Leittechnik einer Anlage mit Linearmotor getriebenen Bahnfahrzeugen - Pottharst, A.

Kreiser, Lothar, Gottlob Frege. Leben – Werk – Zeit, Paperback, Felix Meiner Verlag: Hamburg 2004 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Studentische Veranstaltungskritik: Eine kritische Würdigung der statistischen Anforderungen - Lück, Sonja

Lewis, Albert C., “The Unity of Logic, Pedagogy and Foundations in Grassmann's Mathematical Work”, In: History and Philosophy of Logic 25 (2004), 15–36 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

van Atten, Mark/Kennedy, Juliette, “On the Philosophical Development of Kurt Gödel”, In: Bulletin of Symbolic Logic 9 (2003), 425–476 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete [Wiederabdruck aus MR 2005b:03010])

Wolenski, Jan, “Aletheia in Greek Thought until Aristotle”, In: Annals of Pure and Applied Logic 127 (2004), 339–360 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Smith, David Woodruff, “Mathematical Form in the World”, In: Philosophia Mathematica (3) 10 (2002), 102–129 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Bolzano, Bernard. "Miscellanea mathematica 18", hg. v. Bob van Rootselar/Anna van der Lugt, Frommann-Holzboog: Stuttgart-Bad Cannstatt 2004 (Bernard Bolzano-Gesamtausgabe; II.B.10.2) - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Bolzano, Bernard. "Miscellanea mathematica 19", hg. v. Bob van Rootselar/Anna van der Lugt, Frommann-Holzboog: Stuttgart-Bad Cannstatt 2005 (Bernard Bolzano-Gesamtausgabe; II.B.11.1) - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Hale, Bob/Wright, Crispin, "The Reason’s Proper Study. Essays Towards a Neo-Fregean Philosophy of Mathematics", Clarendon Press: Oxford 2003 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Löfgren, Lars, “Unifying Foundations – to be Seen in the Phenomenon of Language”, In: Foundations of Science 9 (2004), 135–189 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Griffin, Nicholas (Hg.), "The Cambridge Companion to Bertrand Russell", Cambridge University Press: Cambridge 2003 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Bochenski, Joseph M., "Formale Logik", 5. unveränderte Aufl., Karl Alber: Freiburg/München 2002 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Ziche, Paul, „Mathematik als Wissenschaftlichkeitsmodell. Wissenschaftssystematische Konsequenzen variierender Deutungen der Mathematik (1800/1900)“, in: Rudolf Seising/Menso Folkerts/Ulf Hashagen (Hgg.), Form, Zahl, Ordnung. Studien zur Wissenschafts- und Technikgeschichte. Festschrift für Ivo Schneider zum 65. Geburtstag, Franz Steiner Verlag: Stuttgart 2004, 91–106 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Azzouni, Jody, “Proof and Ontology in Euclidean Mathematics”, In: Tinne Hoff Kjeldsen u.a. (Hgg.), New Trends in the History and Philosophy of Mathematics, University Press of Southern Denmark: Odense 2004, 117–133 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Larvor, Brendan, “What is Dialectical Philosophy of Mathematics?”, In: Philosophia Mathematica (3) 9 (2001), 212–229 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

Vandoulakis, Ioannis, “Was Euclid’s Approach to Arithmetic Axiomatic?”, In: Oriens Occidens 2 (1998), 141–181 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete)

„,… Nationalsprache, […] der getreue Spiegel des Fühlens und des nationalen Empfindens’: Zur Polyglossie in Galizien im 19. Jahrhundert“ - Ptashnyk, Stefaniya (Dokumentation der 3. Bayerisch- Ukrainischen Germanistentagung, 28.–30. Oktober 2003, München)

„Unstabile“ feste Wortverbindungen: Zur Dynamik des phraseologischen Sprachbestan-des - Ptashnyk, Stefaniya (Hermes: Journal of Linguistics, No 35/2005)

Wortartikel im elexiko-Kernwortschatz - Ptashnyk, Stefaniya (Elektronische Publikation: http://www.elexiko.de)

Murawski, Roman, “Leibniz’s and Kant’s Philosophical Ideas and the Development of Hilbert’s Programme”, In: Logique et Analyse (N.S.) 45 (2002), 421–437 - Peckhaus, Volker (Mathematical Reviews)

van Atten, Mark/Kennedy, Juliette, “On the Philosophical Development of Kurt Gödel”, Bulletin of Symbolic Logic 9 (2003), 425–476 - Peckhaus, Volker (Mathematical Reviews)

Reck, Erich H., “Dedekind’s Structuralism: an Interpretation and Partial Defense”, Synthese 137 (2003), 369–419 - Peckhaus, Volker (Mathematical Reviews)

Grattan-Guinness, Ivor, “The Mathematics of the Past: Distinguishing its History from our Heritage”, In: Historia Mathematica 31 (2004), 163–185 - Peckhaus, Volker (Mathematical Reviews)

Hallett, Michael/Ulrich Majer (eds.), "David Hilbert’s Lectures on the Foundations of Geometry, 1891-1902", Springer Verlag: Berlin 2004 - Peckhaus, Volker (Mathematical Reviews)

Davis, Martin, “What Did Gödel Believe and When Did He Believe it?”, Bulletin of Symbolic Logic 11 (2005), 194–206 - Peckhaus, Volker (Mathematical Reviews)

Kang, Jinho, “On the Composition of the Prototractatus”, Philosophical Quarterly 55 (2005), 1–20 - Peckhaus, Volker (Mathematical Reviews)

Wolff, Michael, "Abhandlung über die Prinzipien der Logik", Klostermann: Frankfurt a.M. 2004 - Peckhaus, Volker (Mathematical Reviews)

Sasaki, Chikara, "Descartes’s Mathematical Thought", Kluwer: Dordrecht 2003 - Peckhaus, Volker (Mathematical Reviews)

Workshop „Moderne Methoden in der Lexikografie: Theorie und Praxis“ - Ptashnyk, Stefaniya (Sprachreport, Heft 2/2005)

„Scharloth, Joachim: Sprachnormen und Mentalitäten : Sprachbewusstseinsgeschichte in Deutschland im Zeitraum von 1766 – 1785 : Niemeyer, 2005.“ - Ptashnyk, Stefaniya (Zeitschrift für Rezensionen zur germanistischen Sprachwissenschaft, Heft 1/2009)

Mapping the Multitude. Categories in a Process Ontology - Hagengruber, Ruth (Professional Knowledge Management Experiences and Visions. 3rd Conference WM)